Billboard's hottest hot 100 hits - Bronson, Fred (Billboard Books, 2007)
Lists the bestselling popular records by artist, songwriter, producer, label, and subject, as well as the greatest hits arranged by year from 1956 to 2006 and by decade from the fifties through the nineties.